The GPR40 Agonist GW9508 Enhances Neutrophil Function to Aid Bacterial Clearance During E. coli Infections - Souza, Patricia R.; Walker, Mary E.; Goulding, Nicolas J.; Dalli, Jesmond; Perretti, Mauro; Norling, Lucy V. (Frontiers in Immunology, 2020)
G-protein-coupled receptor 40 (GPR40) is known to play a role in the regulation of fatty acids, insulin secretion and inflammation. However, the function of this receptor in human neutrophils, one of the first leukocytes to arrive at the site of infection, remains to be fully elucidated. In the present study, we demonstrate that GPR40 is upregulated on activated human neutrophils and investigated the functional effects upon treatment with a selective agonist; GW9508. Interestingly, GPR40 expression was up-regulated after neutrophil stimulation with platelet-activating factor (PAF, 10nM) or leukotriene B4 (LTB4, 10nM) suggesting potential regulatory roles for this receptor during inflammation. Indeed, GW9508 (1 and 10µM) increased neutrophil chemotaxis in response to the chemokine IL-8 (30ng/ml) and enhanced phagocytosis of E. coli by approximately 50% when tested at 0.1 and 1µM. These results were translated in vivo whereby administration of GW9508 (10mg/kg, i.p.) during E. coli infections resulted in elevated peritoneal leukocyte infiltration with a higher phagocytic capacity. Importantly, GW9508 administration also modulated the lipid mediator profile, with increased levels of the pro-resolving mediators resolvin D3 and lipoxins. In conclusion, GPR40 is expressed by activated neutrophils and plays an important host protective role to aid clearance of bacterial infections.